(untitled) (Journal of Educational Sciences, 2019)
This study was carried out to compare the value orientation of University students in Turkey and Kazakhstan. The sample group consists of 314 university students studying at various departments in the Faculty of Education, Erzincan Binali Yıldırım University, and 340 students at the Faculty of Philosophy and Political Sciences, Al Farabi Kazakh National University. The Personal Information Form and the Schwartz Value Scale were used as data collectiont ools in the study and the t-test was used for independent groups in the analysis of the data. One by one comparisons were made in 10 sub-dimensions of the scale, power, achievement, hedonism, stimulation, self-direction, universalism, benevolence, tradition, conformity, security, and significant differences were found in favor of Turkey in all dimensions on the basis of both countries. Respectively, the values in Turkey is based in order of universality, benevolence, security, self-control, traditional, success, power, harmony, hedonism, and the result of values in Kazakhstan is benevolence, universality, self-control, traditional, success, power, harmony and hedonism. Key words: values, value orientations, university students, kazakhstani students, turkish students.